With a quotation by Engels, dated Januari 4, 1891, under the portrait. Compare BG A4/621 for the photo after which this engraving was made - Scheu, Heinrich,
With a quotation by Engels, dated Januari 4, 1891, under the portrait. Compare BG A4/621 for the photo after which this engraving was made.